The Phosphorylation of CCR6 on Distinct Ser/Thr Residues in the Carboxyl Terminus Differentially Regulates Biological Function - Lu, Mei-Yi; Lu, Syuan-Shao; Chang, Shiann-Luen; Liao, Fang (Frontiers in Immunology, 2018)
CCR6 is a G protein-coupled receptor (GPCR) that recognizes a single chemokine ligand, CCL20, and is primarily expressed by leukocytes. Upon ligand binding, CCR6 activates Gαi heterotrimeric G proteins to induce various potential cellular outcomes through context-specific cell signaling. It is well known that differential phosphorylation of Ser and Thr residues in the C-terminal domains or intracellular loops of GPCRs can generate barcodes that regulate GPCR function by regulating the recruitment of β-arrestins. In this study, we demonstrate that ligand binding to CCR6 induces receptor phosphorylation at Ser/Thr residues in the C-terminal tail, rather than intracellular loops. Using mutagenesis experiments, we determined that distinct clusters of Ser/Thr residues in the C-terminal domain differentially regulate CCL20-induced signaling and cellular response. Substituting the Thr360/Ser361/Thr363 cluster or the Ser370/Ser371 cluster with Ala residues modulated cellular response upon CCL20 stimulation. Notably, receptor internalization, chemotaxis, F-actin distribution, transient ERK1/2 activation and β-arrestin 2 recruitment were oppositely affected by mutating the two clusters, suggesting that phosphorylation of CCR6 C-terminal Ser/Thr residues directs the cell signaling response upon receptor activation. Moreover, activated CCR6 weakly recruited β-arrestin 1 in comparison to β-arrestin 2, and the two arrestin proteins seemed to play overlapping but distinct roles in mediating CCL20/CCR6-induced cellular responses. Taken together, the effects of site-specific Ser/Thr phosphorylation on CCR6 demonstrate the existence of barcodes on the protein that dictate the activation of different cell signaling profiles and lead to distinct biological outcomes.